Common Weedy Plants on Open, Tilled, and Rocky Soil in the Redland Agricultural Area, Miami-Dade County, Florida - Cliff G. Martin; Zachary T. Brym (EDIS, 2022)
This article provides a reference for the most competitive weeds found in south Florida open areas with Rockdale soil. Written by Cliff G. Martin and Zachary T. Brym, and published by the UF/IFAS Agronomy Department, January 2022.